STATISTICAL ANALYSIS OF THE INTERACTION BETWEEN COLD SURGE AND COLD TONGUE PHENOMENA AGAINST RAINFALL AT JAKARTA - Kettaren - Nim: 12813013, Ray
In this study, we investigated the interaction of Cold Surge (CS) and Cold Tongue (CS) phenomena and its impact against rainfall at Indonesia’s territory throughout its climatology period. Both of phenomena occur along with the presence of the Winter Monsoon in the northern hemisphere. The impact of the interaction defined over Jakarta and western part of Java Sea and this study begins from 1981 to 2016. Daily re-analysis sea surface temperature (SST), meridional wind and precipitation datasets being used for identifying CS and CT events. CS and CT identified as daily event. We determine the interaction of CS and CT as a group of an event. To examine the frequency of the result, we used statistical analysis. The result shows that weak CS has the highest frequency while strong CT has the highest frequency too during 1981-2016. Weak CS – strong CT is an interaction group that most often occurs and strong CS – strong CT is an interaction group that most rarely occurs during the climatological period. The average rainfall when the interaction of CS – CT happened can be concluded influencing the rainfall conditions in Jakarta and part of Java Sea. Strong CS – strong CT interaction group has the highest mean rainfall among other groups.